Investigating user preferences towards visualization types with a focus on neuroticism and its implications on mental health - Mohd Zanan, Muhammad Faris Basheer; S. Abd. Aziz, Madihah; Luhana, Krishan Kumar; Keerio, Imran Khan; Shah, Asadullah (Cosmos Scholars Publishing House, 2023)
This study delves into the importance of visualizing mental health data to attain a comprehensive understanding of psychological disorders through the means of data storytelling and information visualization. Utilizing the Five Factor Model, the article investigates the correlation between two prevalent mental health conditions, depression and anxiety, with a specific focus on the neuroticism trait. The researchers aim to underscore the potential of data-driven techniques in shaping mental health interventions and promoting a deeper comprehension of these conditions by exploring the association between neuroticism and various visualization approaches. To achieve this objective, the study employs quantitative research methods to support population association analysis, cause-and-effect analysis, and the assessment of the link between independent and dependent variables. The findings show that neuroticism has no relationship to any sort of visualization type, and this paper presented several explanations for the lack of a relationship between visualization type and neuroticism.